Oligarchic Policies in Bulgaria and Their Public Legitimation - Tsakova, Ivka (Research Papers, 2021)
The content of the article refers to the period of “transition to a market economy and liberal democracy” in Bulgaria after 1989 and the unfolding oligarchization of politics under neoliberal capitalism. The problem posed in the title is clarified by applying the critical method derived from critical social theories (A. Gramsci, C. Crouch, D. Harvey, etc.). Based on working definitions of oligarchic power and oligarchic politics/policies, three ways for public legitimization of oligarchic policies in Bulgaria are outlined: a) redirection of public attention from interests to values; b) reaching a neoliberal consensus in the state, parties and civil society; c) oligarchic capture of the media through neoliberal propaganda.
Keywords: Bulgarian transition; Politics of oligarchy; Neoliberalism